Associations between perceived neighbourhood problems and quality of life in older adults with and without osteoarthritis: Results from the Hertfordshire Cohort Study. (January 2017) - Timmermans, Erik J.; van der Pas, Suzan; Schaap, Laura A.; Cooper, Cyrus; Edwards, Mark H.; Gale, Catharine R.; Deeg, Dorly J.H.; Dennison, Elaine M.
Abstract: This study examined whether the association of quality of life (QoL) with perceived neighbourhood problems is stronger in older adults with osteoarthritis (OA) than in those without OA. Of all 294 participants, 23.8% had OA. More perceived neighbourhood problems were associated with a stronger decrease in QoL over time in participants with OA (B=−0.018; p=0.02) than in those without OA (B=−0.004; p=0.39). Physical activity did not mediate this relationship. Older adults with OA may be less able to deal with more challenging environments.